The Impact of Fetal Growth Restriction on Prenatal 2D Ultrasound and Doppler Study of the Fetal Adrenal Gland - Suphawan Pattamathamakul; Chatuporn Duangkum; Sukanya Chaiyarach; Kiattisak Kongwattanakul; Piyamas Saksiriwuttho; Ratana Komwilaisak; Sathida Chantanavilai; Manasicha Pongsamakthai; Prapassara Sirikarn (Hindawi Limited, 2024)
Conclusion: Both increased IAA PSV and enlarged volumes of the corrected whole adrenal gland and neocortex were found in fetuses with FGR, suggesting significant adrenal gland adaptation in response to chronic intrauterine stress.